Young athletes with ventricular premature beats: Continuing or not intense training and competition?. (4th August 2017) - Parisi, A.; Tranchita, E.; Minganti, C.; Sperandii, F.; Guerra, E.; Calò, L.; Borrione, P.; Pigozzi, F.
Abstract : Isolated ventricular premature beats (VPBs) are commonly found during pre‐participation screening in athletes. Currently, the debate about the role of detraining in reducing the number of VPBs is still open. This study evaluated the arrhythmic risk in a population of young competitive athletes who showed VPBs during eligibility evaluation and that did not undergo detraining but continued practicing competitive sports. 3746 consecutive subjects underwent pre‐participation screening. Athletes who showed VPBs were selected and underwent second level evaluation (Echocardiogram, 24 hour Holter ECG and Exercise test). Athletes were re‐evaluated after a follow‐up period (6‐48 months) while they continued practicing competitive sports. 5.3% of the whole population showed ventricular arrhythmias. 73% of the subjects showed isolated VPBs. 88% of the subjects showed monomorphic VPBs, and 12% of athletes showed polymorphic VPBs. At echocardiogram, there was not any pathology which contraindicated competitive sport activity. At 24 hour Holter ECG recording, mean number of daily VPBs was 1592±3217 (range 0‐16678). At holter ECG follow‐up (16±12 months), the median number of VPBs decreased from 93 (IQR 20‐3065) to a new value of 72 (IQR 2‐1299). Continuing competitive sport in subjects with ventricular arrhythmias even though frequent but with a low grade of complexity and without structural cardiomyopathy does not increase sudden death risk.